(untitled) (Sains Humanika, 2014)
This study aims to compare the mastery level of basic science process skills among upper primary Indian students by gender, school location, and by grade levels. Using an established 36-item Basic Science Process Skills (BSPS) test that assesses the skills of observing, communicating, classifying, measuring, predicting, and inferring with appropriate reliability and validity, the instrument was administered to 379 upper primary Indian students from two rural and two urban national typed primary schools in Perak. The dataset were analysed by gender and by location using an independent samples t-test, and by grade level using one-way ANOVA. The findings indicated that (1) upper primary students failed to achieve the two-third level or 67% in overall BSPS and across all specific BSPS; (2) there was no gender difference in overall BSPS and across all specific BSPS; (3) urban Indian students achieved significantly higher than rural Indian students in overall BSPS and across all specific BSPS; and (4) there was a significant difference in overall BSPS and across all specific BSPS among year 4, 5 and 6 primary Indian students in which the post hoc tests indicated that Year 6 Indian students achieved significantly higher than Year 4 and Year 5 Indian students except for classifying in which there was no significant difference between Year 6 and Year 5 Indian students. Key findings are interpreted and discussed in the context of science pedagogy and inculcation of science process skills.